PENERAPAN METODE FUZZY TSUKAMOTO DALAM MEMBANTU PERENCANAAN PERSEDIAAN BAHAN BAKU KAYU PADA INDUSTRI FURNITUR - Dian Eko Hari Purnomo; Yogi Akbar Sunardiansyah; Amelia Nur Fariza (Industry Xplore, 2020)
The furniture industry is experiencing the problem of uncertainty in determining the optimal amount of wood raw material inventory. Fuzzy logic is one of the methods used to analyze systems that contain uncertainty. This study discusses the application of fuzzy logic in solving the problem of supplying wood raw materials in the furniture industry with the Fuzzy-Mamdani approach. The data used in this study are data on the entry, distribution, and supply of wood raw materials from January to December 2018. The design of the system to obtain output is carried out in the following stages: (a) Formation of fuzzy sets, (b) Application of functions implications, (c) Composition of rules, (d) Affirmation (defuzzification). Solving the problem using the Fuzzy Tsukamoto method is carried out by the Tsukamoto method with the help of Visual Basic software so that the desired results will be obtained on the output variable. From the results of calculations using the Fuzzy Tsukamoto method, it can be analyzed that the comparison between the realized wood raw material inventory with the Fuzzy Tsukamoto approach looks different and the results from the Fuzzy Tsukamoto approach are more optimal.